Motivation and attitude among ESL Learners: A study among secondary school learners / Kemin anak Sumbeh - Sumbeh, Kemin (2011)
This study reveals the motivation and attitude of English language learners in a secondary school in Betong Division. A quantitative research design was chosen in which self-valuated questionnaires adapted from Gardner’s AMTB (1985) were distributed to respondents which were actually the researcher’s language students. The questionnaire was employed to elicit the information about the respondent’s background, as well as to identify their motivation and attitude towards the language learning, particularly English as one of their main paper in the Malaysian Education System. SPSS version 11.05 was employed in the process of data analysis: data screening, data purification, exploratory factor analysis and Re-test Reliability Analysis. . The findings revealed that there is no significant preference in motivation types among respondents but at the same time, a negative direction in relation between integrative and instrumental motivation with gender but recorded a positive relation with grade scored was recorded. A detail analysis of the respondents responses to some of the items, however do provide some clues to the persisting problem in their second language learning. Their reluctance to use the language outside the boundary o f the classroom revealed their practical attitude. It is an irony to their awareness of the language importance to their future. Cross-tabulation of other variables with the demographic background does not reveal significant relationship. However, there is quiet a significant implication of this study towards the language teachers and trainers particularly in relation with some statements in the questionnaire.